САЛТ-ДӘСТҮР ПОЭЗИЯСЫНДА БЕТ АШАР ҚОСЫҚЛАРЫНЫҢ ӨЗИНЕ ТӘН ӨЗГЕШЕЛИКЛЕРИ - Ешимуратова, А.А. (FAN va JAMIYAT, 2022)
This article discusses the genre of “betoshar” its composition, features of the wedding ceremony of the Karakalpak people in order to deeply study the traditions of restoring our national qualities inherited from our ancestors.